The Development of Organic Farming in Europe - Villy Søgaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 1999)
The paper sets out a dynamic framework for analysing the impact of public support on the growth of organic farming in Europe. Although the empirical results are uncertain, it appears that national support and EU certification have accelerated the process of expansion without significantly changing the long-term size of the organic sector.
Keywords: 330; Organic farming; conversion support; logistic growth